2014
DOI: 10.1007/s00170-014-6128-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigate on distribution and scatter of surface residual stress in ultra-high speed grinding

Abstract: The purpose of this study is to investigate the residual stress induced by ultra-high-speed grinding of difficult-tomachine materials considering the thermomechanical coupling effect that is generated due to the friction between diamond tool and workpiece's surface. A three-dimensional finite element method taking the rotational motion of tool into account is proposed. The simulation consists of three operations including loading, unloading, and cooling. The influences of different grinding conditions (grindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Furthermore, based on the simulated grinding work of 40Cr steel with single abrasive grain, Fang and Zhang [125] reported that either tensile or compressive residual stress exists along the grinding direction on the finished surface depending on the different grinding conditions; especially, the compressive or tensile residual stresses may exist simultaneously. Compared with the high-speed grinding (i.e., wheel speed of 60∼120 m/s), the ultra-high-speed grinding (i.e., wheel speed of 180 m/s) could produce compressive residual stress or lower tensile residual stress on the machined surface; meanwhile, the residual stresses along the depth below the Fig.…”
Section: Conventional Speed Grinding and High-speed Grindingmentioning
confidence: 99%
“…Furthermore, based on the simulated grinding work of 40Cr steel with single abrasive grain, Fang and Zhang [125] reported that either tensile or compressive residual stress exists along the grinding direction on the finished surface depending on the different grinding conditions; especially, the compressive or tensile residual stresses may exist simultaneously. Compared with the high-speed grinding (i.e., wheel speed of 60∼120 m/s), the ultra-high-speed grinding (i.e., wheel speed of 180 m/s) could produce compressive residual stress or lower tensile residual stress on the machined surface; meanwhile, the residual stresses along the depth below the Fig.…”
Section: Conventional Speed Grinding and High-speed Grindingmentioning
confidence: 99%
“…Currently, the surface layer (SL) predominant role in ensuring the machine parts durability is generally recognized [1][2][3][4][5][6][7][8][9][10][11][12][13]. Especially the part surface layer, which forming throughout the manufacture technological process, receives the greatest loading during operation.…”
Section: Introductionmentioning
confidence: 99%
“…Influences of grinding parameters on residual stresses have been studied in terms of wheel speed, workpiece speed, cutting depth, material removal rate, wheel characteristics, dressing conditions, and material conditions [4]. It is recommended that generation of residual stress is the result of various mechanical and thermal effects occurring at the machined surface region during grinding.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [5] found that the values of the compressive stresses are decreased with the increase in depth of cut in creep feed grinding with brazed CBN Wheels. Chen et al [4] observed that ultra-high-speed grinding can obtain lower surface residual tensile stress than high-speed grinding. Brinksmeier et al [6] concluded that the increase in depth of cut and/or grinding speed increase the magnitude of tensile residual stresses.…”
Section: Introductionmentioning
confidence: 99%